DJEČJA PORNOGRAFIJA U SVJETLU RAČUNARSKIH KRIVIČNIH DJELA: MEĐUNARODNI STANDARDI I PRAVO BOSNE I HERCEGOVINE - Vladimir M. Simović; Marina M. Simović (Revija za kriminologiju i krivično pravo)
Based on international standards in a number of universal (UN) and regional (Council of Europe) documents, a large number of national legislations, including positive law of Bosnia and Herzegovina, provide for several computer (computer, IT, information, cyber) crimes that violate or endanger various social values by using (or abusing) computers, computer systems or information technology. These are various forms of illegal activities of natural and legal persons, using computer systems, whether it is about old crimes take on new forms (forms of manifestation), or completely new crimes. Among these criminal offenses, computer crimes are especially dangerous for children and youth. In this paper the system of international standards and the basic characteristics of computer crimes, as well as the content of computer crimes as means of production or dissemination of pornographic material in the legal system of Bosnia and Herzegovina are considered.